2014
DOI: 10.1093/humrep/deu326
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of oral mucosal epithelial cell sheets on intrauterine adhesions

Abstract: Transplantation of OMECS offers a reliable method not only to protect the woman's fertility from intrauterine re-adhesion after synechiotomy for IUA or uterine lumen adhesion but also to prevent adhesion after any intrauterine surgery in clinical cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 21 publications
0
34
0
5
Order By: Relevance
“…Recent studies have reported increased expression of fibrotic markers, including collagens I and III, in endometrial tissue adhesions (33). Novel therapeutic approaches to treat the disorder, which have been modeled in rodents, but not yet applied in patients, include transplantation of bone marrow‐derived stem cells (34) and oral mucosal cell sheets (35).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported increased expression of fibrotic markers, including collagens I and III, in endometrial tissue adhesions (33). Novel therapeutic approaches to treat the disorder, which have been modeled in rodents, but not yet applied in patients, include transplantation of bone marrow‐derived stem cells (34) and oral mucosal cell sheets (35).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies using autologous cell sheet‐tissues were performed in the fields of ophthalmology, periodontology, cardiovascular medicine, orthopedics, gastrointestinal surgery, and otolaryngology . Moreover, for treating various diseases, including pneumothorax, diabetes mellitus, hepatic disease, hemophilia, renal dysfunction, endocrinopathy, and uterine disorders, various studies using cell sheet‐tissues are ongoing . In clinical and preclinical studies, OCM will be a powerful tool for evaluating cell sheet‐tissues noninvasively, for example, their thickness, cell condition, and adhesions between layered cell sheets.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44][45][46] Moreover, for treating various diseases, including pneumothorax, diabetes mellitus, hepatic disease, hemophilia, renal dysfunction, endocrinopathy, and uterine disorders, various studies using cell sheet-tissues are ongoing. [47][48][49][50][51][52][53][54] In clinical and preclinical studies, OCM will be a powerful tool for evaluating cell sheet-tissues noninvasively, for example, their thickness, cell condition, and adhesions between layered cell sheets. Due to its noninvasiveness, it is not necessary to fabricate extra tissues for observation, which results in greater cell savings, lower costs, and less preparation times.…”
Section: Discussionmentioning
confidence: 99%
“…The use of human stem cell treatments for the reconstruction of the endometrium following substantial damage and IUA formation has been hypothesized for some time [96], with studies from animal models showing substantial promise in this area of medical treatment [9799]. From the first prospective series in humans, 16 women with substantial hysteroscopically confirmed IUAs were treated by uterine intravascular infusions of BMDSC [100].…”
Section: Introductionmentioning
confidence: 99%
“…Ambulatory methods include office hysteroscopy and HSG, with recurrence of more than mild IUAs likely requiring anesthetic and division. Early reintervention with assessment a few weeks after hysteroscopy rather than several months has been suggested in randomized [75] and retrospective studies [99, 100] to both assess and treat recurrence.…”
Section: Introductionmentioning
confidence: 99%